Pengaruh Kualitas pelayanan dan Perceived Value Terhadap Kepuasan Tamu (studi Pada Tamu MICE di Hotel Truntum) - Riko Andofal; Rian Surenda; Dwi Pratiwi Wulandari (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2023)
The research was based on observations during industrial field experience and pre-research at Truntum Padang hotel, where several obstacles were found related to Service Quality and Perceived Value to Guest Satisfaction of MICE Service Users. The research method is quantitative with a causal relationship. Using nonprobality sampling technique by taking 100 respondents. This study uses a questionnaire to collect data using a Likert scale of 42 statements that have been tested for validity and reliability, the data is described through the analysis requirements test and hypothesis testing using multiple linear regression analysis techniques and the coefficient of determination using SPSS 20.00. Research results: (1) Service quality is in the very good group with a result of 56%. (2) Perceived value is in the good group with a result of 56%. (3) Satisfaction is in the good group with 63% results. Hypothesis testing shows the effect of X1 on Y with Sig. 0.00 <0.5 while t count 5.866> t table 1.9847, so H1 is accepted, the effect of X2 on Y is 0.238> 0.05 and t count 1.186 < t table 1.9847, so H2 is rejected, while the effect of Xl and X2 together on Y is 0.00 <0.05 and F count 63.269> from F table 3.09 so it can be said that H3 is accepted and R Square is 0.556.